A comparative entropy based analysis of tangent hyperbolic hybrid nanofluid flow: Implementing finite difference method. (December 2021) - Hussain, Syed M.; Jamshed, Wasim
Abstract: Due to its application in the industry, heat transport is of crucial relevance. A novel form of nano-fluid known as the hybrid nanofluid helps to increase the thermal transfer capacity of regular fluids and has a larger thermal exponent. The two-part nanoparticle in a standard fluid is connected to the hybrid nanofluids. This study examines the hybrid nanofluid flowing properties and thermal transport passing through a slippy surface. There will be an examination of the forms of Inclined magnetic field, viscous dissipation, inclined joule heating, and thermal radiative impacts. The controlled equations are numerically solved using a numerical methodology, that is the finite difference procedure. This examination has included the hybrid tangent hyperbolic nanofluid which consists of the rich viscous non-Newtonian fluid (CH2 OH)2 (ethylene glycol) of the genre of dual different sorts of nano-solid particles i.e., copper (Cu) and silicon dioxide (SiO2 ). It is worth noting that the heat transmission level of SiO2 -Cu/(CH2 OH)2 which has been steadily increasing compared with the typical nanofluid (Cu-(CH2 OH)2 ). The entropy system is amplified to the Inclined magnetic field, radiative heat flux, Eckert and Weissenberg numbers by assimilation of nanoparticles ratio. Furthermore, SiO2 -Cu/(CH2 OH)2 tangent hyperbolic hybrid nanofluid combinations hold an upper hand in the main aspects of heat transfer efficiency while compared to the Cu-(CH2 OH)2 tangent hyperbolic nanofluid.